Ecoliteracy: Knowledge, Attitudes, and Ecological Behavior of Elementary School Students Using the Multiliteracy Learning Model - Desiana Natalina; Ani Hendriani; Dadan Setiawan; Yusuf Tri Herlambang; Budi Hendrawan; Nunuy Nurjanah (CV. Ksatria Siliwangi, 2023)
TDensity area by buildings than land green moment This resulted problem health and literacy ecological experienced the individual who inhabits it. Focus on research This is literacy ecological covering aspect knowledge cognitive, attitude, and behavior ecological student school base through learning models multiliteracy. Study This is study experiment with the matching pretest posttest control group design, and involved 79 students grade 5 school base in the environment factory area Bandungregency. Data collected use test choice double For measure knowledge and attitude ecological students, and use scale likert For see behavior ecological student. Research results show that knowledge, attitude, and behavior ecological student experience enhancement after get learning using learning models multiliteracy. Response results attitude and behavior ecological student show positive thing.